Ecuador : Fostering Environmentally Sustainable Tourism and Small Business Innovation and Growth in the Galapagos - Valdivieso, Jose; Toth, Bob; Hanna, James; Quintero, Juan (World Bank, Washington, DC, 2012)
Well-managed tourism can be an important contributor to sustainable development, providing incentives to protect the environment and maintain biodiversity, while fostering small business development. A recently completed subcomponent of Ecuador's International Trade and Integration Project, supported by a Bank Loan, demonstrates this win-win situation. This note analyzes tourism, in particular the pressures it creates on the environment in the Galapagos islands, given its stance as the fourth largest industry in Ecuador. Voluntary environmental quality standards certification for tour vessels were addressed by specialists, who developed a strategy, focused on the tourists, and the 60 currently active tour boats. Standards were established to minimize environmental impacts by applying conservation practices to boats, and requiring sensitizing clients to the need for environmental behavior. To this end, stakeholders, including government agencies, conservationists, and local communities participated in developing the "SmartVoyager" standards, a development effort beyond conservation. The International Galapagos Tour Operators Association, made significant inputs to the standards, and pledged to support the certification program. This outreach effort enabled the small boat operators to learn what the standards required; how to comply with the requirements; and, most importantly, why the requirements were included in the standards. After this training and motivation, a number of boat operators began to implement practices specified in the standards. Some lessons address the need to bring small businesses into this initiative early on, to gain strong acceptance and support; that beneficiaries share in the costs, including tourists, tour operators, and the national park; and, that the seemingly commercially advantageous certification, should allow enterprises to become self-supporting once its benefits are demonstrated.